Reciprocal Relationship Between Self-Control Belief and Gaming Disorder in Children and Adolescents: Longitudinal Survey Study - Shimin Zhu; Di Qi (JMIR Serious Games)
Abstract BackgroundChildren and adolescents are often at the crossroads of leisure gaming and excessive gaming. It is essential to identify the modifiable psychosocial factors influencing gaming disorder development. The lay theories of self-control (ie, the beliefs about whether self-control can be improved, also called self-control mindsets) may interplay with self-control and gaming disorder and serve as a promising influential factor for gaming disorder. ObjectiveThis study aims to answer the research questions “Does believing one’s self-control is unchangeable predict more severe gaming disorder symptoms later?” and “Does the severity of gaming disorder symptoms prospectively predict self-control mindsets?” with a 1-year, 2-wave, school-based longitudinal survey. MethodsA total of 3264 students (338 in grades 4‐5 and 2926 in grades 7‐10) from 15 schools in Hong Kong participated in the classroom surveys. We used cross-lagged panel models to examine the direction of the longitudinal association between self-control mindsets and gaming disorder. ResultsA bidirectional relationship was found between self-control mindsets and gaming disorder symptom severity (the cross-lagged path from mindsets to gaming disorder: regression coefficients [bPbPbPbPbPbP ConclusionsOur findings demonstrated the negative impact of gaming disorder on one’s self-control malleability beliefs and implied that promoting a growth mindset regarding self-control might be a promising strategy for gaming disorder prevention and early intervention, especially for girls.